Employing SiO2 nano-particles in conformal and in-cup structures of 8500 K white LEDs - My Hanh Nguyen Thi; Phung Ton That (Bulletin of Electrical Engineering and Informatics, 2021)
SiO2 nano-particles have been examined in a distant phosphor structure for the elevated luminous quality and better consistency of white light-emitting diodes with angular-dependent associated color temperature (CCT). The luminous scattering ability could be increased by applying SiO2 nano-particles contain silicone to the outside of the phosphorus coating. In specific, the strength of blue light at wide angles is increased and differences in CCT can be minimized. In addition, owing to the sufficient refractive indices of silicone-containing SiO2 nanoparticles between the air and phosphorus layers, the luminous flux was improved. This new configuration decreases angular-dependent CCT deviations in the range of -700 to 700 from 1000 to 420 K. In comparison, at a 120 mA driving current, the rise of lumen flux increased by 2.25% relative to an usual distant phosphor structure without SiO2 nano-particles. As a result, in a distant phosphor structure, the SiO2 nano-particles could not only enhance the uniformity of illumination but also enhance the output of light.